2023
DOI: 10.21037/jtd-22-1226
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative detection of pleural adhesions using dynamic chest radiography: prospective analysis

Abstract: Background: To plan a surgical approach and predict the operative time or bleeding volume, it is important to determine the presence of pleural adhesions before surgery. Dynamic chest radiography (DCR)is a new modality that can dynamically capture X-rays, and we assessed the utility of DCR for detecting pleural adhesions preoperatively. Methods:The subjects of this study were those who underwent DCR before surgery from January 2020 to May 2022. The preoperative evaluation was performed by three imaging analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Various classifications have been used in literature based on the presentation of the pleural adhesions (e.g., density, coverage) ( 1 ) and the degree of surgical disturbance ( 6 ). In the work of Watanabe and colleagues, the presence of pleural adhesion was confirmed with intraoperative findings: the coverage of more than 20% of the thoracic cavity and/or dissection time of more than 5 minutes ( 11 ). The criteria include the aspects of the presentation and surgical disturbance, elaboration of the determination of the cut-off value is expected for future reference.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Various classifications have been used in literature based on the presentation of the pleural adhesions (e.g., density, coverage) ( 1 ) and the degree of surgical disturbance ( 6 ). In the work of Watanabe and colleagues, the presence of pleural adhesion was confirmed with intraoperative findings: the coverage of more than 20% of the thoracic cavity and/or dissection time of more than 5 minutes ( 11 ). The criteria include the aspects of the presentation and surgical disturbance, elaboration of the determination of the cut-off value is expected for future reference.…”
mentioning
confidence: 95%
“…A recent study by Watanabe et al investigated the utility of dynamic chest radiography (DCR) in detecting pleural adhesions ( 11 ). DCR is a relatively new X-ray imaging modality for analyzing and diagnosing chronic obstructive pulmonary disease, cystic fibrosis, and pulmonary hypertension.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study published in a previous issue of the Journal of Thoracic Disease , Watanabe et al reported on the diagnostic efficacy of DCR for pleural adhesions ( 15 ). The most substantial novelty of this study is its evaluation of the diagnostic ability of DCR, particularly the LM mode.…”
mentioning
confidence: 99%
“…In a previous study using the FE mode of DCR, pleural adhesions were evaluated on the basis of three abnormal motions (restricted motion, structural tension, and distorted motion) ( 16 ). However, this method is subjective, as the results depend on the skill of the evaluator ( 15 ).…”
mentioning
confidence: 99%